Honokiol ameliorates angiotensin II‐induced hypertension and endothelial dysfunction by inhibiting HDAC6‐mediated cystathionine γ‐lyase degradation. Issue 18 (4th August 2020) - Chi, Zhexi; Le, Truc Phan Hoang; Lee, Sang Ki; Guo, Erling; Kim, Dongsoo; Lee, Sanha; Seo, Seung‐Yong; Lee, Sook Young; Kim, Jae Hyung; Lee, Sang Yoon
Abstract: Hypertension and endothelial dysfunction are associated with various cardiovascular diseases. Hydrogen sulphide (H2 S) produced by cystathionine γ‐lyase (CSE) promotes vascular relaxation and lowers hypertension. Honokiol (HNK), a natural compound in the Magnolia plant, has been shown to retain multifunctional properties such as anti‐oxidative and anti‐inflammatory activities. However, a potential role of HNK in regulating CSE and hypertension remains largely unknown. Here, we aimed to demonstrate that HNK co‐treatment attenuated the vasoconstriction, hypertension and H2 S reduction caused by angiotensin II (AngII), a well‐established inducer of hypertension. We previously found that histone deacetylase 6 (HDAC6) mediates AngII‐induced deacetylation of CSE, which facilitates its ubiquitination and proteasomal degradation. Our current results indicated that HNK increased endothelial CSE protein levels by enhancing its stability in a sirtuin‐3‐independent manner. Notably, HNK could increase CSE acetylation levels by inhibiting HDAC6 catalytic activity, thereby blocking the AngII‐induced degradative ubiquitination of CSE. CSE acetylation and ubiquitination occurred mainly on the lysine 73 (K73) residue. Conversely, its mutant (K73R) was resistant to both acetylation and ubiquitination, exhibiting higher protein stability than that of wild‐type CSE. Collectively, our findings suggested that HNK treatment protects CSE against HDAC6‐mediated degradation and may constitute an alternative for preventing endothelial dysfunction and hypertensive disorders.